Enhancing Electrode Performance by Exsolved Nanoparticles: A Superior Cobalt-Free Perovskite Electrocatalyst for Solid Oxide Fuel Cells - Yang, G.; Zhou, W.; Liu, M.; Shao, Zongping (American Chemical Society, 2016)
The successful development of low-cost, durable electrocatalysts for oxygen reduction reaction (ORR) at intermediate temperatures is critical for broad commercialization of solid oxide fuel cells. Here, we report our findings in design, fabrication, and characterization of a cobalt-free SrFe0.85Ti0.1Ni0.05O3−δ cathode decorated with NiO nanoparticles. Exsolved from and well bonded to the parent electrode under well-controlled conditions, the NiO nanoparticles uniformly distributed on the surface of the parent electrode greatly enhance cathode performance, demonstrating ORR activity better than that of the benchmark cobalt-based Ba0.5Sr0.5Co0.8Fe0.2O3−δ. Further, a process for regeneration of the NiO nanoparticles was also developed to mitigate potential performance degradation due to coarsening of NiO particles under practical operating conditions. As a general approach, this exsolution–dissolution of electrocatalytically active nanoparticles on an electrode surface may be applicable to the development of other high-performance cobalt-free cathodes for fuel cells and other electrochemical systems.